Pollution characteristics, mechanism of toxicity and health effects of the ultrafine particles in the indoor environment: Current status and future perspectives. Issue 3 (1st February 2022) - Ali, Muhammad Ubaid; Lin, Siyi; Yousaf, Balal; Abbas, Qumber; Munir, Mehr Ahmed Mujtaba; Rashid, Audil; Zheng, Chunmiao; Kuang, Xingxing; Wong, Ming Hung
Abstract: Ultrafine particles (UFPs) with an aerodynamic diameter of <0.1 µm are emerging as the most dominant and abundant particulate matter. Human exposure to these particles has increased dramatically, especially in the indoor environment as most of the population spend 80 to 90% time in the indoor environment. Due to the small size, it is believed that these particles will impose more dangerous and aggressive health impacts. However, knowledge of UFPs is still lacking as most of the previous studies focused on PM10 and PM2.5 . The current article aims to provide a critical overview of UFPs sources, composition, physicochemical properties, potential exposure route, toxicity mechanisms, and health impacts to identify the research gaps and future research directions and perspectives. It is commonly observed that inhalation is the dominant route of exposure. Inhaled ultra-fine particles can penetrate deep into the respiratory track, resulting in adverse health impacts, ranging from normal transient of respiratory problems to cardiovascular and respiratory mortality and morbidity, lung cancer, brain disease, mutagenic and carcinogenic impacts. Due to the large surface area, these particles can transport a variety of toxins causing tissue and cell injury, leading to enhanced oxidative stress and inflammation. In order to overcome the environmental burden and health consequences attributed to ultrafine particles, proper air quality guidelines should be introduced and it is suggested that future research should focus on the relationship between health symptoms and UFPs physicochemical properties, especially the mechanics of chemical transformation in human body, their biological behavior, and toxicological effect. Graphical abstract: UF0001